2019
DOI: 10.1111/jgs.16244
|View full text |Cite
|
Sign up to set email alerts
|

Medical Comorbidities of Dementia: Links to Caregivers' Emotional Difficulties and Gains

Abstract: OBJECTIVES To evaluate how eight major medical comorbidities of dementia (arthritis, cancer, diabetes, heart disease, hypertension, lung disease, osteoporosis, and stroke) are associated with caregivers' perceptions of emotional caregiving difficulties and caregiving gains (ie, benefits or rewards from the care role). DESIGN Nationally representative cross‐sectional surveys of community‐dwelling persons living with dementia (PLWDs) and their co‐resident family caregivers in the United States. SETTING The 2011 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 28 publications
0
20
1
Order By: Relevance
“…Many people with dementia have co‐occurring chronic conditions, such as hypertension or arthritis. A national study of caregivers of people with dementia living with additional chronic conditions found that caregivers of people with dementia who had a diagnosis of diabetes or osteoporosis were 2.6 and 2.3 times more likely, respectively, to report emotional difficulties with care compared with caregivers of people with dementia who did not have these co‐occurring conditions 422 …”
Section: Caregivingmentioning
confidence: 99%
“…Many people with dementia have co‐occurring chronic conditions, such as hypertension or arthritis. A national study of caregivers of people with dementia living with additional chronic conditions found that caregivers of people with dementia who had a diagnosis of diabetes or osteoporosis were 2.6 and 2.3 times more likely, respectively, to report emotional difficulties with care compared with caregivers of people with dementia who did not have these co‐occurring conditions 422 …”
Section: Caregivingmentioning
confidence: 99%
“…A9 diabetes or osteoporosis were 2.6 and 2.3 times more likely, respectively, to report emotional difficulties with care compared with caregivers of people with dementia who did not have these co-occurring conditions. 463 Depression and mental health.…”
Section: Burden and Stressmentioning
confidence: 99%
“…Many people with dementia have co‐occurring chronic conditions, such as hypertension or arthritis. A national study of caregivers of people with dementia living with additional chronic conditions found that caregivers of people with dementia who had a diagnosis of diabetes or osteoporosis were 2.6 and 2.3 times more likely, respectively, to report emotional difficulties with care compared with caregivers of people with dementia who did not have these co‐occurring conditions 463 …”
Section: Caregivingmentioning
confidence: 99%
“…We can assume that these kinds of activities are easier for emerging adult students who live with the ill/disabled relative. In addition, caring for a relative with comorbidities brings a risk of emotional difficulties [63] and is associated with reduced social connectedness [64]. The higher psychological distress score for emerging adult students with the emotional care pattern can therefore be explained by both the nature of the caring activity, the living arrangements, and the relative's type of illness/disability.…”
Section: Patterns Of Caring Activities and Mental Healthmentioning
confidence: 99%